Working the day or the night shift? Foraging schedules of Cory’s shearwaters vary according to marine habitat - Dias, Paulo Sousa (2012)
The diel vertical migration of zooplankton and many other organisms is likely to affect the foraging behaviour of marine predators. Among these, shallow divers, such as many seabirds, are particularly constrained by the surface availability of prey items. We analysed the atsea activity of a surface predator of epipelagic and mesopelagic prey, Cory’s shearwater Calonectris diomedea, on its several wintering areas (spread throughout the temperate Atlantic Ocean and the Agulhas Current). Individual shearwaters were mainly diurnal when wintering in warmer and shallower waters of the Benguela, Agulhas and Brazilian Currents, and comparatively more nocturnal in colder and deeper waters of the Central South Atlantic and the Northwest Atlantic. Nocturnality also correlated positively with bathymetry and negatively with sea-surface temperature within a single wintering area. This is possibly related to the relative availability of epipelagic and mesopelagic prey in different oceanic sectors, and constitutes the first evidence of such flexibility in the daily routines of a top marine predator across broad spatial scales, with clear expression at population and individual levels